2003
DOI: 10.1074/jbc.m305413200
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of the HIV-1 Vpr N Terminus

Abstract: The 96-residue human immunodeficiency virus (HIV) accessory protein Vpr serves manifold functions in the retroviral life cycle including augmentation of viral replication in non-dividing host cells, induction of G 2 cell cycle arrest, and modulation of HIV-induced apoptosis. Using a combination of dynamic light scattering, circular dichroism, and NMR spectroscopy the N terminus of Vpr is shown to be a unique domain of the molecule that behaves differently from the C-terminal domain in terms of self-association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
59
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 76 publications
(192 reference statements)
6
59
0
Order By: Relevance
“…Recombinant CypA (Sigma) was immobilized at a concentration ranging from 4200 to 11200 response units using standard amine-coupling chemistry in three flow cells, and a further flow cell without CypA was used as a control. The peptides Vpr , Vpr [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] , Vpr [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] , and respective proline mutants were dissolved at concentrations ranging from 1 to 250 M in a running buffer (10 mM Hepes, 150 mM NaCl, 50 M EDTA, 0.005% Tween 20, pH 7.4) and were injected over the flow cells at a flow rate of 5 l/min. Data were collected at a rate of 2.5 Hz during the 120-s association and dissociation phase.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Recombinant CypA (Sigma) was immobilized at a concentration ranging from 4200 to 11200 response units using standard amine-coupling chemistry in three flow cells, and a further flow cell without CypA was used as a control. The peptides Vpr , Vpr [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] , Vpr [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] , and respective proline mutants were dissolved at concentrations ranging from 1 to 250 M in a running buffer (10 mM Hepes, 150 mM NaCl, 50 M EDTA, 0.005% Tween 20, pH 7.4) and were injected over the flow cells at a flow rate of 5 l/min. Data were collected at a rate of 2.5 Hz during the 120-s association and dissociation phase.…”
Section: Methodsmentioning
confidence: 99%
“…in Vivo-Our recent finding (19) of unusually large amounts of cis proline conformations about the imidic bond for two of the proline residues in the N terminus of Vpr suggested that Vpr folding may require a PPIase enzyme activity. Since both Vpr and CypA are present in HIV-1 virions, and CypA binds to HIV-1 CA and promotes virus infectivity, we investigated whether Vpr and CypA also interact.…”
Section: Biochemical Evidence For Cypa-vpr Interaction In Vitro Andmentioning
confidence: 99%
See 3 more Smart Citations